Hybrid Controller with Fuzzy Logic Technique for Three Phase Half Bridge Interleaved Buck Shunt Active Power Filter. Issue 2 (2020) - Echalih, S.; Abouloifa, A.; Janik, J.M.; Lachkar, I.; Hekss, Z.; Chaoui, F.Z.; Giri, F.
Abstract: This paper addresses a new control of three phase half bridge interleaved buck shunt active power filter (HBIB-SAPF). We aim for a control strategy achieving simultaneously, the two following objectives: i) compensation of harmonic currents and reactive power absorbed by nonlinear loads for satisfying a power factor correction; ii) regulation of the HBIB converter DC capacitor voltage. To meet the above objectives, the proposed controller structure consists of two loops. The inner loop is designed using a hybrid dynamical approach to model the system, the hybrid automaton is proposed to deal with the compensation topic by switching between the different operative modes, which is conditioned by some invariance and transition conditions. The outer loop is built up based on fuzzy logic control (FLC), applied to regulate the DC bus voltage of three phase HBIB-SAPF. It is confirmed, via simulation results in Matlab/ SimPowerSystems & Stateflow toolbox that the proposed controller actually achieves the objectives it is designed for.